Analysis Intuitive Leadership and Mentoring on Employee Performance (Literature Review) - Kamal, Fahmi; Sidjabat, Sonya; Purwoko, Harry; Kamsariaty, Kamsariaty; Sjarifudin, Didin (East Asian Journal of Multidisciplinary Research, 2023)
This paper aims to provide an in-depth understanding of how the combination of intuitive leadership and mentoring can be a key factor in achieving competitive advantage and sustainable growth in the modern business context. The method used is qualitative where the source of findings comes from articles related to the variables in this paper, with a time span of ten years and this proof to strengthen and provide an implementation result in a result in a scientific paper or article. Intuitive leadership and mentoring on employee performance, it can be concluded that these two elements play an important role in shaping a productive work environment that supports individual growth. Intuitive leadership, with its emphasis on instinct-based decision-making and emotional intelligence, creates responsive and adaptive leaders. This dynamic work environment allows employees to thrive, creating a culture of flexibility and innovation. Mentoring also contributes significantly to employee performance, through personalized and ongoing mentoring. With mentors in place, employees can experience increased job satisfaction, engagement and development of specialized skills.